Comprehensive Study of the Morphology and Anatomy of Mango (Mangifera indica) as a Differentiator from Other Species: A Literature Review - Muhammad Abdul Jabar; Jasmine Augi Nadifa; Maria Sulistiyowati (Jurnal Serambi Biologi, 2024)
Mango (Mangifera indica) is one of the plants from the Anacardiaceae family that is most widely cultivated in Indonesia because of its high economic value. As a result of plant cultivation, Mangifera indica has very diverse varieties. Apart from that, the existence of other plants that have almost the same body structure, especially from other genus Mangifera, makes it important to know the true morphology and anatomy of Mangifera indica. So, this research aims to determine the morphology and anatomy of Mangifera indica. The main method used in this research is literature study from various articles on the internet. The results of this research discuss the morphology and anatomy of the leaves, stems, roots, flowers, fruit and seeds of Mangifera indica in detail and comprehensively so that they are easier to understand. Also added are several studies regarding Mangifera indica varieties which aim to differentiate between the morphology and anatomy of Mangifera indica and its varieties. The conclusion of this research states that Mangifera indica is a plant that has unique morphological and anatomical characteristics, which can differentiate this species from other species in the same genus. Keywords: Morphology, Anatomy, Mangifera indica